2023
DOI: 10.3390/molecules28052306
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Carnosic Acid: Insight into Its Mechanisms of Action

Abstract: Carnosic acid is a diterpenoid abundantly present in plants belonging to the genus Rosmarinus and Salvia of the family Lamiaceae, accounting for their application in traditional medicine. The diverse biological properties of carnosic acid that include antioxidant, anti-inflammatory, and anticarcinogenic activities have instigated studies on its mechanistic role, providing further insights into its potential as a therapeutic agent. Accumulating evidence has established the relevance of carnosic acid as a neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 91 publications
1
13
0
Order By: Relevance
“…Neuroprotective effects of natural and synthetic antioxidants such as ED, EB, and CA have been widely documented, and the intracellular mechanisms of their action are rather well recognized [ 20 , 24 , 26 , 27 , 28 , 42 , 43 ]. However, our comparative in vitro study using various neuronal cell models and experimental settings only to some extent supported the general view on the biosafety of these compounds as well as the high efficacy of them in protecting neuronal cells against various harmful insults.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuroprotective effects of natural and synthetic antioxidants such as ED, EB, and CA have been widely documented, and the intracellular mechanisms of their action are rather well recognized [ 20 , 24 , 26 , 27 , 28 , 42 , 43 ]. However, our comparative in vitro study using various neuronal cell models and experimental settings only to some extent supported the general view on the biosafety of these compounds as well as the high efficacy of them in protecting neuronal cells against various harmful insults.…”
Section: Resultsmentioning
confidence: 99%
“…It should be added that the importance of glia cells in CA-mediated protection was also highlighted in previous studies [ 65 , 70 ]. When taking into account the potential usefulness of CA in the treatment of neurodegenerative diseases [ 28 , 71 ], it is justified to consider it as an active component of nanodrugs, which could balance its unfavorable pharmacokinetic profile [ 12 ]. To this end, it has been reported that nanocarrier-packaged CA ameliorated glia-mediated neuroinflammation and improved cognitive function in an Alzheimer’s disease model [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the use of a citrus flavonoid, nobiletin, attenuated the methylglyoxal-induced toxicity [ 87 ]. Other polyphenolic compounds, including ss-caryophyllene and carnosic acid, and camellia oil were also demonstrated to show anti-inflammatory activity and thus act as potential neuroprotective compounds [ 85 , 88 , 89 ]. The RAGE-induced activation of CD5L, an inflammatory protein, leads to the decreased brain volumes, while higher circulating soluble RAGE (s-RAGE), which functions as a decoy receptor for RAGE, was associated with increased brain volumes in AD models [ 90 ].…”
Section: Rage and Gut Microbiotamentioning
confidence: 99%
“…Carnosic acid and its derivatives are one of the strongest natural antioxidants produced by some plant species. Carnosic acid also exhibits antibacterial, antifungal, antiviral, anti-inflammatory, anticancer and neuroprotective properties [ 1 , 2 , 3 ]. It can also be a preventive and supportive measure in the treatment of many diseases, including Alzheimer’s, Parkinson’s and COVID-19 [ 4 ] as well as some cancers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%